Y = -3x - 1......so we sub in -3x - 1 in for y in the other equation
2x + 5y = 12
2x + 5(-3x - 1) = 12....now distribute the 5 through the parenthesis
2x - 15x - 5 = 12...add 5 to both sides
2x - 15x = 12 + 5..combine like terms
-13x = 17...divide both sides by -13
x = -17/13
now sub in -17/13 for x in the other equation
y = -3x - 1
y = -3(-17/13) - 1
y = 51/13 - 1
y = 51/13 - 13/13
y = 38/13
so the solution is (-17/13, 38/13)
Hello,
The answer is "16".
Reason:
Just divide 12 by 3/4:
12×4=48÷3=16
1×3=3÷3=1
16/1=16
Therefore they can make 16 pizza crusts!
If you need anymore help feel free to ask me!
Hope this helps!
~Nonportrit
-4 is the x-intercept for your equation
Answer:
1/2(3)-2/3(8)
3/2-9/3
<u>3</u>-<u>9</u>
2.3
<u>9</u><u>-</u><u>3</u><u>2</u>
6
<u>-23</u>
6